Research Methods for the Self-Study of Practice
250 p.
Keywords: This volume presents 13 studies that provide concrete and authentic illustrations of self-study as it naturally unfolds across different educational settings. Each chapter provides in-depth descriptions of the context, method choices and processes used for self-study research, highlighting how researchers gather, analyze and make sense of data. All of these studies offer rich examples of the recursive processes so important in self-study research. The first section highlights the use of text as data to examine the meaning and value of teacher education practices. The second features self-studies using discourse and dialogue as data and often as actual analysis tools for examining practice. The third presents studies in which different forms of visual representations are used as data that illuminate the ideas, assumptions and experiences underlying practice. The final section presents self-studies focused on the impact of practice on teacher education programs, students, and faculty-student interactions.